FABP4 gene expression in subcutaneous and visceral adipose tissue in patients with obesity and type 2 diabetes mellitus - K. V. Dracheva; I. A. Pobozheva; K. A. Anisimova; Z. M. Hamid; A. P. Sapojnikova; S. G. Balandov; D. I. Vasilevsky; S. N. Pchelina; V. V. Miroshnikova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Obesity is associated with a high risk of developing concomitant diseases such as: metabolic syndrome, type 2 diabetes mellitus (DM2), cardiovascular pathology. FABP4 (fatty acid binding protein) is the specific lipid chaperone and an important protein for the function of adipose tissue and is one of the adipocytokines secreted by adipose tissue.The objective of the study was to investigate the FABP4 gene expression in subcutaneous and visceral adipose tissue (SAT and VAT) in patients with obesity and DM2.Methods and materials. SAT and VAT samples were obtained during bariatric surgery (N=43, BMI>35): obese with DM2 (N=21), obese without DM2 (N=22). Samples for the control group without obesity (N=15, BMI<30) were obtained during planned operations on the abdominal cavity. FABP4 mRNA level was estimated by real-time PCR.Results. It has been demonstrated that the mRNA level of the FABP4 gene in SAT and VAT is reduced in obesity, regardless of the manifestation of DM2 (p<0.01). A negative correlation was observed between the mRNA level of the FABP4 gene in adipose tissue and the BMI index (for SAT: r=—0.327, p = 0.016; for VAT: r=—0.304, p = 0.024).Conclusion. The expression level of FABP4 gene in AT can act as a marker of AT dysfunction in obesity.